L’atelier de l’historienne : ‘The Life of John Hutchinson’ de Lucy Hutchinson - Claire Gheeraert-Graffeuille (Etudes Epistémè)
This essay proposes to highlight the historian’s craft in Lucy Hutchinson’s biography of her husband, “The Life of John Hutchinson of Owthorpe in the Country of Nottinghamshire”, by examining in turn her use of sources, her art of composition, as well as the ideological purpose of her work. Favouring a rational analysis of facts and the art of narration, her story bears the mark of humanist historiography, but it is also in keeping with a politically committed vision of history, essentially perceived as the work of an all-powerful providence. In this respect, “The Life of John Hutchinson” should be regarded as an important history of the period that compares favourably with the historical writings of Lucy Hutchinson’s contemporaries.